Evidence for the Involvement of the Chemosensory Protein AgosCSP5 in Resistance to Insecticides in the Cotton Aphid, Aphis gossypii - Li, Fen (Insects, 2021)
SIMPLE SUMMARY: Insect chemosensory proteins (CSPs) are potential targets for insect pest control strategies and are proposed to function in insect chemoreception, because they play a role in crop host location by binding and transporting odorant molecules. They are also thought to have other functions, for example, in tissue regeneration and in insecticide resistance, because they also express in nonolfactory tissues and are capable of binding insecticides. However, there are few reports that provide direct evidence for this proposal. In this study, we discovered gene gain-and-loss among aphid populations, possibly associated with different insecticide resistance, and then identified and cloned a CSP gene responsive to insecticide treatments. The introduction of such gene in Drosophila fruit flies made the transgenic flies less sensitive to the treatment of different insecticides. Our study advances the research of insect CSP functions and offers valuable new information to target CSPs for pest management. ABSTRACT: It has been speculated that insect chemosensory proteins (CSPs) may have additional roles beyond olfaction. In this study, the phylogenetic and genomic analyses of the CSPs of the cotton aphid, Aphis gossypii, revealed the presence of gene gain-and-loss among different aphid field populations. Differential expressions of eight CSP genes were demonstrated after treatments with insecticides of different modes of action. The expression of AgosCSP5 was significantly upregulated by the insecticide treatments in a dose-dependent manner. The Drosophila flies overexpressing AgosCSP5 were significantly less susceptible to the insecticides, omethoate, imidacloprid and cypermethrin but not to deltamethrin and tau-fluvalinate, compared with control flies. The transgenic Drosophila flies exhibited an LC(50) resistance ratio of 2.6 to omethoate, compared with control flies. Likewise, the mortality of the transgenic flies to imidacloprid and cypermethrin was significantly lower than that of the control flies (p < 0.01). Homology modelling, molecular docking and dynamic simulation supported the interactions and revealed a higher stability of AgosCSP5/insecticide complexes than AgosCSP5/semiochemical complexes. Our study demonstrates for first time the in vivo evidence for the involvement of CSP genes in insecticide resistance of crop insect pests and provides new insights of the newly discovered CSP-mediated insect resistance mechanism to insecticides.